The immunostimulatory role of an Enterococcus-dominated gut microbiota in host protection against bacterial and fungal pathogens in Galleria mellonella larvae - Upfold, Jennifer; Rejasse, Agnès; Nielsen-Leroux, Christina; Jensen, Annette Bruun; Sanchis-Borja, Vincent (Frontiers in Insect Science, 2023)
Understanding the intricate interplay between the gut microbiota and the immune response in insects is crucial, given its diverse impact on the pathogenesis of various microbial species. The microbiota’s modulation of the host immune system is one such mechanism, although its complete impact on immune responses remains elusive. This study investigated the tripartite interaction between the gut microbiota – pathogens – host response in Galleria mellonella larvae reared under axenic and conventional conditions. The influence of the microbiota on host fitness during infections was evaluated via two different routes: oral infection induced by Bacillus thuringiensis subsp. galleriae (Btg), and topical infection induced by Metarhizium robertsii (Mr). We observed that larvae without a microbiota can successfully fulfill their lifecycle, albeit with more variation in their developmental time. We subsequently performed survival assays on final instar larvae, using the LD50 dose of Btg and Mr. Our findings indicated that axenic larvae were more vulnerable to an oral infection of Btg, specifically, a dose that was calculated to be half-lethal for the conventional group resulted in 90-100% mortality rate in the axenic group. Through a dual-analysis experimental design, we could identify the status of the gut microbiota using 16S rRNA seq and assess the level of immune-related gene expression in the same group of larvae at basal conditions and during infection. This analysis revealed that the microbiota of our conventionally reared population is dominated entirely by four Enterococcus species, and these species potentially stimulated the immune response in the gut, due to the increased basal expression of two AMPs, Gallerimycin and Gloverin, in the conventional larvae compared to the axenic Furthermore, E. mundtii isolated from the gut of conventional larvae showed inhibition activity against Btg in vitro. Lastly, other immune effectors, namely phenoloxidase activity in the hemolymph and total ROS/RNS in the gut was tested to further investigate the extent of the stimulation of the microbiota on the immune response. These findings highlight the immune-modulatory role of the Enterococcus-dominated gut microbiota, an increasingly reported microbiota assemblage of laboratory populations of Lepidoptera, and its influence on the host's response to oral and topical infections.